Leading, coincident and lagging indicators in the U.S. business cycles - Bon, Andrew; Janíčko, Martin, 1983-; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
This thesis focuses mainly on analysing leading indicators of business cycles within the USA since the 1960s until the present, while providing theoretical background to the coincident and lagging indicators. United States is a country with incredibly rich amounts of data, which enable a thorough analysis of individual variables. First part is dedicated to different theories that explain the behaviour of cyclical fluctuations, such as a monetarist, Keynesian, or real business cycle approaches are included, followed by defining individual cyclical indicators with the provision of examples. Second part consists of actual analysis starting with dating post-war cycles and real GDP development. Three leading indicators are then analysed and evaluated, specifically the amounts of building permits issued, spread between a 10-year Treasury constant maturity bill and Federal funds rate and finally the unemployment insurance claims. Evaluation is based on individual success rates obtained from historical data. The third and final chapter attempts to forecast the economic outlook of the current business cycle using obtained data from the previous chapter. Conclusion provides an overall summary of individual parts along with pointing out the main findings.
Vedoucí práce: Martin Janíčko
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses